Receptor selectivity between the G proteins Gα12 and Gα13 is defined by a single leucine‐to‐isoleucine variation. Issue 4 (2nd January 2019) - Mackenzie, Amanda E.; Quon, Tezz; Lin, Li‐Chiung; Hauser, Alexander S.; Jenkins, Laura; Inoue, Asuka; Tobin, Andrew B.; Gloriam, David E.; Hudson, Brian D.; Milligan, Graeme
ABSTRACT: Despite recent advances in structural definition of GPCR–G protein complexes, the basis of receptor selectivity between G proteins remains unclear. The Gα12 and Gα13 subtypes together form the least studied group of heterotrimeric G proteins. G protein–coupled receptor 35 (GPR35) has been suggested to couple efficiently to Gα13 but weakly to Gα12 . Using combinations of cells genome‐edited to not express G proteins and bioluminescence resonance energy transfer–based sensors, we confirmed marked selectivity of GPR35 for Gα13 . Incorporating Gα12 /Gα13 chimeras and individual residue swap mutations into these sensors defined that selectivity between Gα13 and Gα12 was imbued largely by a single leucine‐to‐isoleucine variation at position G.H5.23. Indeed, leucine could not be substituted by other amino acids in Gα13 without almost complete loss of GPR35 coupling. The critical importance of leucine at G.H5.23 for GPR35–G protein interaction was further demonstrated by introduction of this leucine into Gαq, resulting in the gain of coupling to GPR35. These studies demonstrate that Gα13 is markedly the most effective G protein for interaction with GPR35 and that selection between Gα13 and Gα12 is dictated largely by a single conservative amino acid variation.—Mackenzie, A. E., Quon, T., Lin, L.‐C., Hauser, A. S., Jenkins, L., Inoue, A., Tobin, A. B., Gloriam, D. E., Hudson, B. D., Milligan, G. Receptor selectivity between the G proteins Gα12 and Gα13 is defined by a single leucine‐to‐isoleucine variation. FASEB J. 33, 5005–5017 (2019). www.fasebj.org